The contingent value of social resources: Entrepreneurs' use of debt-financing sources in Western China - Zhang, Yanlong (Journal of Business Venturing, 2015)
This study shows that entrepreneurs' use of debt-financing sources is conditioned by the resources embedded in their social networks. More business or political contacts increase entrepreneurs' probability of using formal financial sources, and more urban ties increases their probability of using informal sources. However, the effects of business and bureaucratic ties are contingent on community-level institutional trust and on firms' age. Business ties have greater positive impact on the probability of using formal financial sources for older firms and for those in regions with a higher level of institutional trust, while the impact of bureaucratic ties on these firms is weaker.